Impressionism - Pickeral, Tamsin (The World's Greatest Art, 2018)
Bringing to life the work of artists such as Monet, Renoir and Pissarro, Impressionism takes the reader back to Nineteenth-century Paris to explore one of the most influential, lively and popular art movements in the history of art. A comprehensive, but accessible guide.